NOx formation processes in rotating detonation engines - Van Beck, Caleb; Raman, Venkat (Frontiers in Aerospace Engineering, 2024)
High-fidelity simulations of RDEs with H 2 -Air-NO x chemistry are employed to study NO x emissions in such devices. Discrete injection of gaseous hydrogen fuel and continuous injection of air oxidizer is used at various mass flow rate conditions in several 3D RDE simulations to understand resulting NO x production behaviors. Simulations are also performed for two different injector configurations, one in which air is injected axially into the detonation chamber (Axial Air Inlet (AAI)) and one in which air is injected radially (Radial Air Inlet (RAI)). It is seen that the AAI RDE produces much less NO x than the RAI RDE, mainly due to the weaker waves seen in this system as a result of parasitic combustion losses from product gas recirculation. Parasitic combustion does lead to NO x formation in its own right, but the emissions levels from this process are negligible compared to emissions stemming directly from detonation processes. In regards to detonation strength in particular, it is generally seen that detonation strength increases with increasing mass flow rate, in turn increasing peak pressure, peak heat release and NO x emissions levels. Nevertheless, even the highest recorded NO x levels at the combustor exit in this study remain on the same order of magnitude as compared to gas turbine exhaust emissions levels, supporting the claim that significant differences between detonative and deflagrative combustion do not necessarily lead to significant differences in NO x levels. Overall, this study provides greater understanding into the behaviors of NO x formation in RDEs and how these behaviors are affected by changes in operating parameters.